ЕFFECTIVENESS OF THE DRUG MELATONIN WOMEN OF REPRODUCTIVE AGE WITH ABNORMAL UTERINE BLEEDING AND COMBINED EXTRAGENITAL PATHOLOGY - E. N. Tananakina (Акушерство, гинекология и репродукция, 2016)
Сurrently optimization of therapy approaches is the actual in management of women with abnormal uterine bleeding combined with extragenital pathology. Study objective: to increase the treatment effectiveness of abnormal uterine bleeding in fertile women with presence of concomitant extragenital pathology by studying the hormonal levelsand to develop pathogenetically substantiated treatment regimen. Materials and  Methods: a prospective trial of 96 fertile women with abnormal uterine bleeding concomitant extragenital pathology. All patients received a standard hemostatictherapy, 48 women additionally administered melatonin (Group 1), and 48 women received standard therapy without melatonin (group 2). 23 patients without any gynecologic and extragenital pathology comprised Group 3 (control group). Results: melatonin usage during treatment of uterine bleeding in fertile women with combined extragenital pathology: to increasing levels of cortisol, which indicates the possibility of a more rapid formation of the adaptation syndrome; stabilizes the endogenous melatonin; normalizes the ratio of estrogen and progesterone levels, optimizing hormonal balance, regardless of the original background and level of the breach, and thus increases the efficiency of the treatment of uterine bleeding, which is important for practical medicine.